Low-power clustering scheduling algorithm for wireless sensor nodes in the internet of things. Issue 2 (28th February 2020) - Qiu, Jianxin; Mo, Lianguang
Aiming at the problems of high energy consumption and long packet forwarding time existing in the existing wireless sensor node scheduling algorithm, a low-power scheduling algorithm for wireless sensor nodes in the internet of things based on clustering power consumption balanced scheduling is proposed. In this algorithm, a distributed balancing control model is used for optimised deployment design of wireless sensor nodes and design of node transmission route of the internet of things; the full-network power consumption equalisation model is adopted for path planning of wireless sensor nodes; based on an adaptive route forwarding protocol, clustering balancing control of wireless sensor nodes is performed; the minimum power consumption load is taken as the constraint cost to perform optimised design of clustering forwarding scheduling algorithm for wireless sensor nodes in the internet of things. Simulation results show that in clustering scheduling of wireless sensor nodes in the internet of things, this method costs relatively low power consumption, provides good energy equalisation of the full network, controls the network energy efficiency well, and provides high success forwarding rate of clustering scheduling of sensor nodes and good overall network performance, it has high application advantages.